If it's not what You are looking for type in the equation solver your own equation and let us solve it.
42=3(2-6h)
We simplify the equation to the form, which is simple to understand
42=3(2-6h)
Reorder the terms in parentheses
42=+(+6-18h)
Remove unnecessary parentheses
+42=+6-18h
We move all terms containing h to the left and all other terms to the right.
+18h=+6-42
We simplify left and right side of the equation.
+18h=-36
We divide both sides of the equation by 018 to get h.
h=-2
| z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 | | c-80=36 | | X=38-(-x) | | 3(x+4)-(x+5)=x+4 | | =7+4(x+5) | | f=6q-4 | | -23b=35b | | .23x+.45=8-.32x | | 3x+-7+2x=9 | | 3x-8=5x+3 | | 18x^2-25x=-8 | | 0=-16t^2+60 | | (24)5= | | =7x+4(x+5) | | 4(x-6)+4=6x-8 | | 2r^2+18r+33=0 | | 2x+8=63 | | log(5x+70)=2 | | -55=3x+7x+5 | | =3(x+2)+5x | | 2(x-7)-1=-5(6-x) | | -1+x+x=13 | | 2(x+3)-3x+8=6(x-5)+2 | | 6x+1=-7 | | =3(x+2)+5z | | 0-4(-2)=0 |